Parental teaching of nonprejudiced values toward sexual minorities during adolescence - Padilla-Walker, Laura; Jankovich, Meg O.; Archibald, Corinne (Frontiers in Developmental Psychology, 2024)
The current study examined adolescents' nonprejudiced values toward sexual minorities over three years to determine change over time, as well as parenting and child characteristics as predictors of initial levels and change in values over time. Participants included 573 US adolescents (M age at Wave 1 = 14.56, SD = 1.68, range 12-17; 49% identifying as female; 82% completely heterosexual) and their mother (n = 573, 83% completely heterosexual) and father (n = 341, 99% completely heterosexual), all of whom responded to surveys given annually over three years, starting in 2020. Growth curve analysis suggested that adolescents' nonprejudiced values toward sexual minorities increased from ages 14-16 for both males and female. Results also suggested that both maternal and paternal teaching of nonprejudiced values were consistent predictors of initial levels of adolescent nonprejudiced values, and mothers' teaching was associated with increases in nonprejudiced values over time, over and above other parenting variables like parental warmth and frequency of parental communication about sexual minority topics. The discussion focuses on the importance of parental teaching of nonprejudiced values on the development of adolescents' own nonprejudiced values.